2002
DOI: 10.1126/science.1069325
|View full text |Cite
|
Sign up to set email alerts
|

Atom-Resolved Imaging of Dynamic Shape Changes in Supported Copper Nanocrystals

Abstract: In situ transmission electron microscopy is used to obtain atom-resolved images of copper nanocrystals on different supports. These are catalysts for methanol synthesis and hydrocarbon conversion processes for fuel cells. The nanocrystals undergo dynamic reversible shape changes in response to changes in the gaseous environment. For zinc oxide-supported samples, the changes are caused both by adsorbate-induced changes in surface energies and by changes in the interfacial energy. For copper nanocrystals support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

48
906
1
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,182 publications
(966 citation statements)
references
References 35 publications
(33 reference statements)
48
906
1
11
Order By: Relevance
“…Prominent examples in which TEM was used to gain insights into dynamic structure changes of catalysts are the restructurings of Cu surfaces of a Cu/ZnO catalyst in different gas atmospheres (see also Figures 5 and 6),46, 47 carbon nanofiber growth on a Ni catalyst during methane decomposition,14 and the refacetting of Pt nanocrystals during CO oxidation in a nanoreactor at 1 bar and at elevated temperatures 89…”
Section: Advancing the Characterization Methods: Following Dynamics mentioning
confidence: 99%
See 2 more Smart Citations
“…Prominent examples in which TEM was used to gain insights into dynamic structure changes of catalysts are the restructurings of Cu surfaces of a Cu/ZnO catalyst in different gas atmospheres (see also Figures 5 and 6),46, 47 carbon nanofiber growth on a Ni catalyst during methane decomposition,14 and the refacetting of Pt nanocrystals during CO oxidation in a nanoreactor at 1 bar and at elevated temperatures 89…”
Section: Advancing the Characterization Methods: Following Dynamics mentioning
confidence: 99%
“…Systems composed of several components often feature strong metal–support interactions. Changing redox potentials of the reaction mixtures may lead to differing adhesion between metal particles and the oxide support, which in turn might result in morphological changes (Figure 4 d),13, 46 or decoration effects47, 48, 49, 50 on the metal surface. In extreme cases this may lead to composite formation (Figure 4 c) 51…”
Section: Snapshots On Working Catalysts: Case Studies Unravelling Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these results are encouraging, recent work has demonstrated that surface structures can vary dramatically in UHV environments from those appropriate to the working conditions of industrial catalysts 20. This has led to an explosion of interest in in situ TEM, where materials are studied under more realistic environmental conditions 21, 22, 23.…”
mentioning
confidence: 99%
“…Since different nanoparticle structures may have varying catalytic activity,13 an understanding of the different particle types observed gives additional insight into catalytic performance. This is particularly important in cases where particle morphology is affected by the environment 20, 21, 22. In systems such as these, in situ high spatial resolution EDS is required to observe the true nanostructures and their compositional distribution as shown in Figure 3 f. …”
mentioning
confidence: 99%